An intriguing case of B-acute lymphoblastic leukemia – addressing the diagnostic pitfalls - Yesodharan, Jyotsna; Vidyadharan, Geeta; Jojo, Annie (Indian Journal of Case Reports, 2019)
Acute leukemia often presents with symptoms due to bone marrow failure. But with atypical presentations, the diagnosis may not be straight forward and requires thorough clinical examination followed by carefully selected and interpreted investigations. We present a case of acute leukemia in a child who was admitted with pain and swelling of foot. In absence of classical features, leukemia was not initially suspected and even on subsequent biopsy, the diagnosis could not be picked up, requiring thorough re evaluation. We have hereby made an effort to analyse the pitfalls in this case to help practising clinicians and pathologists who might encounter similar scenarios.